2018
DOI: 10.1182/bloodadvances.2018021592
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MEK and ATR is effective in a B-cell acute lymphoblastic leukemia model driven by Mll-Af4 and activated Ras

Abstract: Infant B-cell acute lymphoblastic leukemias (B-ALLs) that harbor MLL-AF4 rearrangements are associated with a poor prognosis. One important obstacle to progress for this patient population is the lack of immunocompetent models that faithfully recapitulate the short latency and aggressiveness of this disease. Recent whole-genome sequencing of MLL-AF4 B-ALL samples revealed a high frequency of activating RAS mutations; however, single-agent targeting of downstream effectors of the RAS pathway in these mutated ML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Nonetheless, recent publications have reported that using fetal cell types and carefully regulated levels of MLL fusion oncoproteins may improve the lineage fidelity of murine MLL -r leukemia model systems. In one case, inducible Mll -AF4 knock-in models that must be kept on a mixed genetic background exhibit ~30% B-ALL with many still succumbing to AML [ 64 , 65 ] Using knock-in models from the Rabbitts’ laboratory, several groups have found that progenitors exhibit an embryonic period of sensitivity to Mll -AF4 or Mll -ENL transformation [ 66 , 67 ]. For example, Malouf and Ottersbach [ 66 ] and Barrett et al [ 68 ] reported that fetal liver lymphoid-primed progenitors exhibit a preleukemic phenotype dependent on Mll -AF4 expression but fall short of producing full-blown B-ALL.…”
Section: Model Systems For Studying Mll -R B-all Evolution Under Car T Cell Pressurementioning
confidence: 99%
“…Nonetheless, recent publications have reported that using fetal cell types and carefully regulated levels of MLL fusion oncoproteins may improve the lineage fidelity of murine MLL -r leukemia model systems. In one case, inducible Mll -AF4 knock-in models that must be kept on a mixed genetic background exhibit ~30% B-ALL with many still succumbing to AML [ 64 , 65 ] Using knock-in models from the Rabbitts’ laboratory, several groups have found that progenitors exhibit an embryonic period of sensitivity to Mll -AF4 or Mll -ENL transformation [ 66 , 67 ]. For example, Malouf and Ottersbach [ 66 ] and Barrett et al [ 68 ] reported that fetal liver lymphoid-primed progenitors exhibit a preleukemic phenotype dependent on Mll -AF4 expression but fall short of producing full-blown B-ALL.…”
Section: Model Systems For Studying Mll -R B-all Evolution Under Car T Cell Pressurementioning
confidence: 99%
“…Moreover, the activation of the DDR pathway is accompanied by the increase of cell proliferation, suggesting the DDR pathway disorder and DNA damage response in our mouse model. 31 Several studies have stated that the decreased DNA repair efficiency caused by DNA repair deficiencies promotes genetic instability, thus increasing individual susceptibility to cancer, 32-34 whereas others have shown that tumor cells could activate the DNA damage repair to repair damaged DNA, enhancing tumor cells’ survival even at high levels of DNA damage. 35,36 Our data prove that upregulation of AID in BCR-ABL1 + B-ALL following inflammatory stimulation is capable of increased expression of DNA damage repair genes such as Ercc1 , Lig1 , Xrcc1 , Pnkp , and Mutyh .…”
Section: Discussionmentioning
confidence: 99%
“…These patients were also characterised by high residual MRD after induction 5,52 . RAS ‐mutated ALL may be susceptible to targeting through MEK inhibitors 103 . Sotorasib, recent approved for KRAS G12C‐mutated solid tumours may also serve as a paradigm for RAS inhibition in ALL 104 …”
Section: Lesions Detected Using a Combination Of Molecular Analysesmentioning
confidence: 99%
“…5,52 RAS-mutated ALL may be susceptible to targeting through MEK inhibitors. 103 Sotorasib, recent approved for KRAS G12C-mutated solid tumours may also serve as a paradigm for RAS inhibition in ALL. 104 MYC, BCL2 and/or BCL6 MYC rearrangements involving either the light or heavy chain of the immunoglobulin gene lead to the highly proliferative Burkitt lymphoma/leukaemia.…”
Section: Rasmentioning
confidence: 99%